Konsep ‘Dialogika’ dan Perubahan Model Pembelajaran Sekolah Minggu di GKPI Dame Dr. I.L. Nommensen Resort Saitnihuta, Kabupaten Tapanuli Utara - Ririn Purba; Nuzul Solekhah (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2023)
This paper tries to explain how the Sunday School learning strategy is carried out by Sunday School teachers, and the changes in the learning model that are applied during and after the Covid-19 pandemic. This research uses qualitative-descriptive by conducting in-depth interviews with Sekolah Minggu teachers and GKPI Dame Dr. I.L. Nommensen Saitnihuta, Tarutung. By using the dialogue concept of Paulo Freire, this research shows that teaching and learning activities in Sekolah Minggus provide a free space for critical thinking processes. Teachers can provide a more creative and dialogical learning atmosphere to students. The material for Sunday School activities comes from an agenda book entitled 'Ajarlah Mereka' which the GKPI head office issued by adjusting the contents of the Bible. Students are more reflective in absorbing moral education and applying Christian faith. Teachers conduct regular evaluations, mobilize study rooms and arrange worship arrangements during and after the Covid-19 pandemic takes place. Reflective evaluation of a range of different situations can lead to changes in the dialogical learning model. Teachers and students will be in an equal stage, which is both learning to reflect the gospel and Christian moral values ​​in everyday life.